Answer:
9
Step-by-step explanation:
hello
the question here is
![3\sqrt[]{7}(14-4\sqrt[]{56})](https://tex.z-dn.net/?f=3%5Csqrt%5B%5D%7B7%7D%2814-4%5Csqrt%5B%5D%7B56%7D%29)
step 1
multiply through the bracket by the coeffiecient
![\begin{gathered} 3\sqrt[]{7}(14-4\sqrt[]{56}) \\ (3\sqrt[]{7}\times14)-(3\sqrt[]{7}\times4\sqrt[]{56}) \\ (14\times3\sqrt[]{7})-3\sqrt[]{7}\times4\sqrt[]{4\times14} \\ (42\sqrt[]{7})-3\sqrt[]{7}\times8\sqrt[]{14} \\ (42\sqrt[]{7})-\lbrack(3\times8)\sqrt[]{7\times14} \\ 42\sqrt[]{7}-24\sqrt[]{98} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%203%5Csqrt%5B%5D%7B7%7D%2814-4%5Csqrt%5B%5D%7B56%7D%29%20%5C%5C%20%283%5Csqrt%5B%5D%7B7%7D%5Ctimes14%29-%283%5Csqrt%5B%5D%7B7%7D%5Ctimes4%5Csqrt%5B%5D%7B56%7D%29%20%5C%5C%20%2814%5Ctimes3%5Csqrt%5B%5D%7B7%7D%29-3%5Csqrt%5B%5D%7B7%7D%5Ctimes4%5Csqrt%5B%5D%7B4%5Ctimes14%7D%20%5C%5C%20%2842%5Csqrt%5B%5D%7B7%7D%29-3%5Csqrt%5B%5D%7B7%7D%5Ctimes8%5Csqrt%5B%5D%7B14%7D%20%5C%5C%20%2842%5Csqrt%5B%5D%7B7%7D%29-%5Clbrack%283%5Ctimes8%29%5Csqrt%5B%5D%7B7%5Ctimes14%7D%20%5C%5C%2042%5Csqrt%5B%5D%7B7%7D-24%5Csqrt%5B%5D%7B98%7D%20%5Cend%7Bgathered%7D)
Answer:
y = -1/2 | x+3|
Step-by-step explanation:
y = f(x + C) C > 0 moves it left
C < 0 moves it right
y = Cf(x) C > 1 stretches it in the y-direction
0 < C < 1 compresses it
y = −f(x) Reflects it about x-axis
Our parent function is
f(x) = |x|
We want it 3 units left
y = f(x + 3)
y = |x+3|
Then reflected across the x axis
y = −f(x)
y = -|x+3|
Then shrink by 1/2 vertically
y = Cf(x)
y = -1/2 | x+3|
A= P(1+r)^t, where P= initial value, r= interest rate in %, and t = number of years.
However, if there isa decrease in value, the formula becomes:
A= P(1-r)^t and in our case :
A = 30,000(1- 0.24)^t OR A = 30,000(0.76)^t
12• (0.25) • (-8) ÷ 1/3 • 5
3• (8) ÷ 1/3 • 5
24 • 1/3 • 5
8 • 5
40
Until the second step is ok.
in the third step, she multiplied the 1/3 term instead if dividing it
24 ÷ 1/3 . 5
24 ÷ 5/3
72/5